Аналіз та оцінка забезпечення основними ресурсами виробничої діяльності металургійних підприємств України - Борисенко, О.Є. (Економіка промисловості, 2013)
На основі багатофакторного регресійного аналізу забезпечення основними ресурсами ви-робничої діяльності металургійних підприємств України за період з 2005 по 2012 р. визначено фактори впливу на еластичність змін загального результату. Запропоновано як один із напрямів удосконалення механізму управління ресурсним забезпеченням виробничої діяльності підприєм-ства використовувати отримані рівняння множинної регресії, що дозволить підвищити конкурентоcпроможність металопродукції за рахунок використання внутрішніх резервів підприємства.
Ключові слова: виробничі ресурси, ресурсна база, металургійне підприємство, забезпечення ресурсами, багатофакторний регресійний аналіз. На основе многофакторного регрессионного анализа обеспечения основными ресурсами производственной деятельности металлургических предприятий Украины за период с 2005 по 2012 г. определены факторы влияния на эластичность изменений общего результата. Предложено, как одно из направлений усовершенствования механизма управления ресурсным обеспечением производственной деятельности предприятия использовать полученные уравнения множественной регрессии, что позволит повысить конкурентоспособность металлопродукции за счет использования внутренних резервов предприятия.
Ключевые слова: производственные ресурсы, ресурсная база, металлургическое предприятие; обеспечение ресурсами, многофакторный регрессионный анализ. Relevance of research is caused by a crisis state of the metallurgical branch which reason is an insufficiency level of providing with the main resources of production activity. Therefore, development and deployment of the effective actions directed on formation of such a resource base which will allow functioning successfully in the market competitive environment that is impossible without the comprehensive analysis and the assessment level of providing with all necessary resources. That's why production has to become a priority task of the metallurgical enterprise.
The research objectives are the determination of security by the main resources of production activity for the metallurgical enterprise and search of the directions of their rational use for increasing the competitiveness of the Ukrainian steel products.Objects of research are the main productive resources and their influence on activity results of the metallurgical enterprise.
Based on the information given by metallurgical enterprises in financial statements and industry statistical data, the factorial analysis and assessment of resource providing of production activity of the metallurgical enterprises of Ukraine are carried out. The assessment of influence of separate factors on elasticity of changes of the general result was carried out by a method of individual share of an indicator. The carried-out multiple-factor analysis of enterprises production activity allowed establishing the role and extent of influence of the main resources use on the level of sales income. The received equations of multiple regression will allow not only estimating the results of activity of metallurgical enterprise, but also proving the long-term plans and administrative decisions more precisely.
Keywords: production activity, resource base, metallurgical enterprise, providing with resources, influence factors, multiple-factor regression analysis.